Pengendalian Sampah Plastik, Penanggulangan Banjir, dan Penguatan Kapasitas UMKM di Desa Getasan, Kecamatan Petang, Kabupaten Badung - I Putu Iwan Pramana Putra; Ni Luh Putu Indiani (Postgraduated Community Service Journal, 2024)
Getasan Village is one of the seven villages in Petang District. In addition to plantations, Getasan Village also has potential in the livestock sector. From the observation results, there are a number of problems faced by Getasan Village, the first is the lack of public awareness in utilizing plastic bottle waste. Second, the lack of water infiltration in the area of Village Temple and Dalem Temple, Getasan Village. Finally, many small MSMEs still cannot use social media to promote their businesses. The solution we provide for the first problem is to provide early education to elementary school children. The solution to the second problem is the installation of biopores around the Village Temple and Dalem Temple areas of Getasan Village. The solution to the last problem is the socialization of marketing strategies using social media, specifically Instagram. The success of activities is measured using indicators: the achievement of training objectives, the achievement of planned targets, and the sustainability of the program. The level of achievement of these three indicators shows an average value of above 75 percent so that this service activity has been running well. Programs in these community service activities need to be maintained in sustainability with cooperation between the government and the community so that they can increase awareness in recycling plastic bottle waste to provide more benefits, pay attention to the biopores that have been installed so that they are properly maintained, socialization about strategies in marketing products online must also be emphasized periodically so that MSME actors can continue to maintain their social media always update.